The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.5713/ajas.2008.70013
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Genes Related to Egg Production in the Liver of Taiwan Country Chickens

Abstract: The purpose of this study was to detect expression of genes related to egg production in Taiwan Country chickens by suppression subtractive hybridization. Liver samples of mRNA extraction from two Taiwan Country chicken strains (L2 and B), originated from the same population but with very distinct egg production rates after long-term selection for egg and meat production respectively. Two-way subtraction was performed. The hepatic cDNA from the low egg production chickens (B) was subtracted from the hepatic cD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In this process, the hypothalamus produces gonadotropin-releasing hormone-I (GnRH-I) which triggers pituitary gland (adenohypophysis) to release FSH and LH, and stimulates the secretion of estradiol (E2) and progesterone (P4) in ovary while ovulation 19 . Hitherto, several studies have focused to uncover the molecular mechanism associated with egg production performance in chicken 10,20,21 . However, the differential gene expression and key pathways mediating the egg production process across hypothalamic-pituitary-ovarian (HPO) axis are yet to be uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…In this process, the hypothalamus produces gonadotropin-releasing hormone-I (GnRH-I) which triggers pituitary gland (adenohypophysis) to release FSH and LH, and stimulates the secretion of estradiol (E2) and progesterone (P4) in ovary while ovulation 19 . Hitherto, several studies have focused to uncover the molecular mechanism associated with egg production performance in chicken 10,20,21 . However, the differential gene expression and key pathways mediating the egg production process across hypothalamic-pituitary-ovarian (HPO) axis are yet to be uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al (2006) identified two SNPs in the uncoupling protein gene which are associated with daily percent lay. Ding et al (2008) showed that the expression of apoB and PURH genes in liver changed after selection for egg production. In order to identify more DNA markers that are associated with egg production in chickens, the present study selected chicken BMPR-IB as a candidate gene to characterize its polymorphisms and analyze their associations with egg production.…”
Section: Discussionmentioning
confidence: 99%
“…Management and feeding practices in the starter, grower and/or developer phases can alter the body weight gain, growth curve, early egg weight and sexual maturity of the pullets and consequently egg production. Furthermore, advances in genetic selection make today's pullets quite different from those of only a few years ago (Flock, 1998;Jackson, 2006;Ding et al, 2008). Therefore, information on feeding programs for egg-type pullets to point of lay is still required to today's or improved pullets achieve an adequate sexual maturity in terms of body size at first egg, weight of the first egg and days to first egg, and subsequently the production characteristics of laying hens (Zhong et al, 2007;Sungu, 2007).…”
Section: Introductionmentioning
confidence: 99%